A novel coupled biokinetic-equilibrium model to capture oyster metal bioaccumulation in a contaminated estuary (Sydney estuary, Australia). (August 2016) - Lee, Jung-Ho; Richards, Russell G.; Birch, Gavin F.
Abstract: Enriched concentrations of metal contaminants have been reported in surficial sediments and tissues of aquatic organisms in Sydney estuary, New South Wales, Australia. Dietary ingestion of contaminated, suspended sediments is potentially a major route of metal exposure to the filter-feeder Saccostrea glomerata . A dynamically coupled biokinetic-equilibrium bioaccumulation model was developed to explore sediment-oyster-metal uptake interactions. The biokinetic component simulated the sediment dynamics and oyster uptake and loss kinetics while the ion equilibrium model accounted for the metal speciation reactions. Results of a laboratory-based mesocosm experiment as well as data from the literature were used to parameterise the model. The model demonstrated a good fit of the experimental data and indicated that dissolved and particulate organic matter were important determinants of metal bioavailability to this species. The model served also as a unique tool to formulate testable hypotheses and help to better explain the bioaccumulation patterns observed from the experiment. Highlights: Novel model was able to replicate oyster bioaccumulation and depuration patterns. Organic matter complexation dominated speciation for 6 studied metals. Organic matter controlled oyster metal uptake from dissolved + particulate sources. The model explored deeper into experimental results and helped form new hypotheses.